1990
DOI: 10.1029/ja095ia05p06237
|View full text |Cite
|
Sign up to set email alerts
|

Postsunset rise of F layer height in the equatorial region and its relation to the F layer dynamo polarization fields

Abstract: The ionosonde data are studied for equatorial station, Thumba, to delineate various features of the evening height rise of F layer. Sharp increase of h'F and h_F2 is obß 13 served •n the postsunset period for high solar activity. Seasonal variation is observed in this increase of h'F and it is maximum for equinox months. For summer months, there is a delay of about an hour in the time of occurrence of h'F (peak) as compared to winter and equinox months. This delay is shown to be associated with the delay in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…The driving force for the polarization field, which generates the vertical drift or zonal electric field, is the zonal neutral wind. Goel et al (1990) have shown that the polarization field is dependent upon the Eregion density, so its effect will be maximum when both the conjugate points in the E-region correspond to the F-region at the equator sunset. Thus, during equinoxes, with the sunset in the E-region being simultaneous, polarization fields that developed in the equatorial F-region are maximum, showing a prereversal enhancement to be maximum and consequently, the post sunset IEC value.…”
Section: Discussionmentioning
confidence: 99%
“…The driving force for the polarization field, which generates the vertical drift or zonal electric field, is the zonal neutral wind. Goel et al (1990) have shown that the polarization field is dependent upon the Eregion density, so its effect will be maximum when both the conjugate points in the E-region correspond to the F-region at the equator sunset. Thus, during equinoxes, with the sunset in the E-region being simultaneous, polarization fields that developed in the equatorial F-region are maximum, showing a prereversal enhancement to be maximum and consequently, the post sunset IEC value.…”
Section: Discussionmentioning
confidence: 99%
“…In many investigations the rate of change of h ′ F is used to get the vertical drift of base height of F layer [ Goel et al , 1990; Subbarao and Krishna Murthy , 1994; Oyekola , 2009]. However the vertical apparent drift obtained from h ′ F measurements deviate considerably from true vertical E × B drift during early and late evening hours due to effects of chemical recombination.…”
Section: Data Used and Quantitative Estimate Of Magnetic Activitymentioning
confidence: 99%
“…It has been suggested [e.g., Heelis et al , 1974; Tsunoda , 1985; Batista et al , 1986; Goel et al , 1990] that the longitudinal gradient of integrated Pedersen conductivity (LGIPC) in the E region at sunset time can play a positive role in strengthening the EPRE magnitudes. Tsunoda [1985] has shown that the occurrence maxima in scintillation activity at a given longitude are coincident with time of the year when the sunset is simultaneous at the conjugate E layer.…”
Section: Description Of the Model For The Eprementioning
confidence: 99%
“…The study of the seasonal variation of V p is therefore not suitable for the determination of the exclusive influence of LGIPC in the E region on V p . In connection with the variation of V p with solar flux, Goel et al [1990] using E region model by Muggleton [1975] found that because of the variation in electron density from low to high solar flux period, the LGIPC in the E region increases by a factor of two. They suggested that theoretical calculations of V p incorporating the above variation in the LGIPC in the E region be made to assess the role of these gradients in explaining observed variations in V p with increase of solar flux.…”
Section: Description Of the Model For The Eprementioning
confidence: 99%
See 1 more Smart Citation